1999
DOI: 10.1007/s007750050315
|View full text |Cite
|
Sign up to set email alerts
|

EPR properties of mixed-valent μ-oxo and μ-hydroxo dinuclear iron complexes produced by radiolytic reduction at 77 K

Abstract: Radiolytic reduction at 77 K of oxo/hydroxo-bridged dinuclear iron(III) complexes in frozen solutions forms kinetically stabilized, mixed-valent species in high yields that model the mixed-valent sites of non-heme, diiron proteins. The mixed-valent species trapped at 77 K retain ligation geometry similar to the initial diferric clusters. The shapes of the mixed-valent EPR signals depend strongly on the bridging ligands. Spectra of the Fe(II)OFe(III) species reveal an S = 1/2 ground state with small g-anisotrop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0
1

Year Published

2001
2001
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 0 publications
1
33
0
1
Order By: Relevance
“…In MMOH ox , the high-spin ferric irons are antiferromagnetically coupled to form a diamagnetic ground state that is EPR silent. [98,100,117,118] These studies demonstrate that the diiron site of MMOH ox is affected by binding of MMOB but not of MMOR. EXAFS studies of MMOH ox showed no evidence for REVIEWS Soluble Methane Monooxygenase short 1.75 ± 1.80 FeÀO bonds characteristic of {Fe 2 -(m-oxo)} 4 units, and optical spectra similarly lacked absorbances at 350 and 500 ± 600 nm that are typical of oxo-bridged diferric complexes.…”
Section: Spectroscopic Characterization Of Mmohmentioning
confidence: 68%
“…In MMOH ox , the high-spin ferric irons are antiferromagnetically coupled to form a diamagnetic ground state that is EPR silent. [98,100,117,118] These studies demonstrate that the diiron site of MMOH ox is affected by binding of MMOB but not of MMOR. EXAFS studies of MMOH ox showed no evidence for REVIEWS Soluble Methane Monooxygenase short 1.75 ± 1.80 FeÀO bonds characteristic of {Fe 2 -(m-oxo)} 4 units, and optical spectra similarly lacked absorbances at 350 and 500 ± 600 nm that are typical of oxo-bridged diferric complexes.…”
Section: Spectroscopic Characterization Of Mmohmentioning
confidence: 68%
“…D/J mixing) as previously assumed (see eq 8 and eq 11; g A = 2.0). 67 This conclusion applies both to weakly coupled systems, like the alkoxo-bridged complex 1 , and strongly coupled systems, such as those that contain an oxo bridge. …”
Section: Discussionmentioning
confidence: 95%
“…As a means of determining the core structure of 1-OH relative to the HO-Fe IV -O-Fe IV =O open core of 4 , the latter was subjected to radiolytic reduction at 77 K,48 a temperature at which the ligands are expected to be essentially immobile, in order to compare the Mössbauer spectra of the radiolytically reduced species with those derived from ferrocene reduction of 4 . Figure 10A shows a 4.2 K Mössbauer spectrum of 4 prior to reduction, prepared as described previously 23.…”
Section: Resultsmentioning
confidence: 99%